Fugiendum necne sit in persecutione— Zur rhetorischen Strategie und Disposition von Tertullians Traktat de fuga in persecutione. - Greb, Daniel (Vigiliae Christianae, 2020)
In his treatise de fuga in persecutione Tertullian argues that flight is not allowed for any Christian in times of persecution. As persecution originates in God and his will, there is no possibility to flee and avoid it. Such a behaviour would be nothing else than apostasy and would result in the loss of eternal life. Only by submitting oneself completely to God and his providence and the guidance of the Holy Spirit (Paraclete) it is possible to endure persecution and fulfil God's demand for steadfastness. To convince his addressee Fabius, Tertullian gives his treatise a classical rhetorical disposition and arranges his arguments according to the partes orationis. This article investigates the rhetorical substance of the treatise and outlines its disposition as a deliberative speech. It is demonstrated, how Tertullian's rhetoric influences and strengthens his argumentation.